Channel modeling of in-vivo THz nanonetworks: State-of-the-art and research challenges - Papanikolaou, Vasilis K.; Karagiannidis, George K. (Lecture Notes of the Institute for Computer Sciences, Social-Informatics and Telecommunications Engineering, LNICST, 2018)
Recently, it has been proposed, that nanodevices can be injected in the human body and perform non-invasive medical diagnostics. However, due to their small size, a plethora of such nanodevices need to be used in practical applications, thus, creating a nanonetwork, which collects the information and communicates with out-of-body nodes. For these networks, several models have been proposed for the THz channel in the in-vivo scenario. Most of them are based on well-defined theories and physical laws, while some of them are based on experiments. In this paper, we review the state-of-the-art of channel modeling of in-vivo communications in the THz band and discuss future trends and research challenges.
Created from Fastlane, Scopus look-up
Keywords: Channel modeling; In-vivo communication; Nanotechnology; Terahertz nanonetworks